Digitalisasi Peradilan di Indonesia Tengah: Studi Implementasi E-Court dan E-Litigasi di Pengadilan - Lahilote, Hasyim Sofyan; Soleman , Frangky; Hasan, Faradila; Basri, Rusdaya; Lahilote, Azizah (Syariah: Jurnal Hukum dan Pemikiran, 2024)
The implementation of electronic court systems in Indonesia has gained momentum with the issuance of PERMA No. 7 of 2022 on Electronic Case Administration and Court Proceedings. This study aims to analyze the implementation of e-Court and e-Litigation in the Bitung and Praya Religious Courts, focusing on identifying factors that influence the level of adoption and effectiveness of the system. Using an empirical juridical method with a qualitative approach, this research combines in-depth interviews with 12 key informants (including court presidents, vice presidents, judges, and clerks), direct observation for 3 days in each court, and documentation analysis. The results showed a low level of adoption, with the use of e-Court in Bitung only 9.26% and Praya 8.70%, while e-Litigation was even lower (0.54% in Bitung and 0.23% in Praya). The significant difference in case volume between the two courts (367 cases in Bitung and 3,814 cases in Praya) does not correlate with the level of technology adoption. The main barriers include limited digital infrastructure, low technological literacy and user preference for conventional services. The study recommends the development of a multilevel policy that takes into account local characteristics, the strengthening of digital literacy programs through partnerships with educational institutions, and a tiered incentive system to encourage the use of electronic services.